Classification Systems of Cleft Lip, Alveolus and Palate: Results of an International Survey. (February 2023) - Houkes, Ruben; Smit, Johannes; Mossey, Peter; Don Griot, Peter; Persson, Martin; Neville, Amanda; Ongkosuwito, Edwin; Sitzman, Tom; Breugem, Corstiaan
Objective: This study aimed to identify commonly used classification systems by cleft providers around the world, including the perceived indications and limitations of each system. Design: A cross-sectional survey. Participants: A total of 197 registrants from three international cleft/craniofacial meetings. Interventions: Participants were sent a web-based questionnaire concerning cleft classification systems. Main Outcome Measures: Frequency of commonly used classification systems, their perceived indications and limitations. Results: A total of 197 respondents from 166 different centers completed the questionnaire. Healthcare professionals from all disciplines responded, with the most frequent respondents being plastic surgeons (38.1%), maxillofacial surgeons (28.4%) and orthodontists (23.9%). Eighteen different classification systems were in use. The most frequently used systems were the International Statistical Classification of Diseases and Related Health Problems (ICD-10) (35.5%), LAHSHAL (34.0%), and Veau (32.5%) classification systems. Most respondents (32.5%) indicated that anatomical and morphological characteristics are essential components of a classification system. However, respondents indicated that their current classification systems lacked sufficient description of cleft extension and severity. Conclusions: Great variety in the use of classification systems exists among craniofacial specialists internationally. The results recommend the usage of the LAHSHAL classification of OFCs, due to its comprehensiveness, relatively high implementation rate globally, convenience of usage and complementarity with the ICD-10 system. Moreover, it can overcome deficiencies inextricably linked to ICD-10, such as incapacity to describe laterality and clefts of the alveolus. More international exposure to the merits of using the LAHSHAL classification system would be highly recommended.